IN VITRO DEGRADATION OF POLYDIOXANONE (PDO) LIFTING THREADS IN HYALURONIC ACID (HA). - Suárez, Dubraska; Maldonado, Gladys J Velazco de; Ortiz, Reynaldo; Garcia-Guevara, Victor; Miller-Kobisher, Blanca (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2019)
Background: Recently, some clinicians have proposed implanting PDO threads imbibed in hyaluronic acid (HA). However, this is controversial since PDO sutures are hydrophilic and the presence of HA could increase the rate of hydrolysis. Aim: To demonstrate the degradation of PDO lifting threads in HA through ultramicroscopy. Materials and methods: Three, one cm long, segments of 23G PDO threads, where immersed in 1.5 ml non-crosslinked hyaluronic acid in previously labeled, sterile microcentrifuge tubes. These were observed by ultramicroscopy at 4x and 10x after 24, 48 and 72 hours. Results: Microphotographs taken after 24 hours already show structural changes in the fibers, presenting an increase in interlaminar spaces and dilution of violet pigmentation. At 48 hours, degradation continues. PDO hygroscopy is observed as aqueous content between the peripheral layers and the central core of the thread. Some fibers show breakage, and there is an increase in interlaminar and interfibrillar spaces. At 72 hours, as the pigment is released, larger empty spaces are observed in the central column of the thread, and there is disorganization of the peripheral fibrils with fraying all along the fiber. Conclusions: Hyaluronic acid induces rapid biodegradation of the PDO thread by hydrolysis beginning 24 hours after contact of the thread with the biomaterial. We hypothesize that non-crosslinked hyaluronic acid is a powerful catalyzing agent for hydrolytic degradation of the PDO thread, since this thread is highly hydrophilic. Thus, we suggest that clinically embedding PDO threads with HA will only accelerate biodegradation of the suture. Key words: Lifting threads, polydioxanone, hyaluronic acid, biodegradation, PDO hydrolysis